Destabilization of the Internal Situation as One of the Main Threats to the Security of Russian Federation - KUSA, Natalia (Przegląd Strategiczny, 2018)
For the first time internal security has been clearly articulated in Russian National Security Strategy of December 2015. That is when the so-called colour revolutions and “radical social groups which use nationalist and extremist religious ideologies, foreign and international nongovernmental organisations, as well as private citizens who act against the Russian territorial integrity and destabilise political processes” have been deemed the most significant challenges to the Russian security, together with the North Atlantic Alliance and the United States of America. As a response to such defined threats, Russian legislation introduced solutions that attempt to prevent the danger. The aim of this article is to answer the question, whether Russian authorities treat the destabilisation of internal situation as one of the main challenges to the Russian security, and if yes, what are the indications of that? Does Russian legislation (especially from the last few years), actions of the Russian authorities and Russian subject literature, include evidence confirming this hypothesis?